Examination of diverse iron-chelating agents for the protection of differentiated PC12 cells against oxidative injury induced by 6-hydroxydopamine and dopamine - Hašková, Pavlína; Applová, Lenka; Jansová, Hana; Homola, Pavel; Franz, Katherine J; Vávrová, Kateřina; Roh, Jaroslav; Šimůnek, Tomáš (Scientific reports, 2022)
Labile redox-active iron ions have been implicated in various neurodegenerative disorders, including the Parkinson's disease (PD). Iron chelation has been successfully used in clinical practice to manage iron overload in diseases such as thalassemia major; however, the use of conventional iron chelators in pathological states without systemic iron overload remains at the preclinical investigative level and is complicated by the risk of adverse outcomes due to systemic iron depletion. In this study, we examined three clinically-used chelators, namely, desferrioxamine, deferiprone and deferasirox and compared them with experimental agent salicylaldehyde isonicotinoyl hydrazone (SIH) and its boronate-masked prochelator BSIH for protection of differentiated PC12 cells against the toxicity of catecholamines 6-hydroxydopamine and dopamine and their oxidation products. All the assayed chelating agents were able to significantly reduce the catecholamine toxicity in a dose-dependent manner. Whereas hydrophilic chelator desferrioxamine exerted protection only at high and clinically unachievable concentrations, deferiprone and deferasirox significantly reduced the catecholamine neurotoxicity at concentrations that are within their plasma levels following standard dosage. SIH was the most effective iron chelator to protect the cells with the lowest own toxicity of all the assayed conventional chelators. This favorable feature was even more pronounced in prochelator BSIH that does not chelate iron unless its protective group is cleaved in disease-specific oxidative stress conditions. Hence, this study demonstrated that while iron chelation may have general neuroprotective potential against catecholamine auto-oxidation and toxicity, SIH and BSIH represent promising lead molecules and warrant further studies in more complex animal models.
Keywords: přetížení železem; Iron; buňky PC12; Catecholamines; Deferoxamine; Oxidative Stress; Animals; dopamin; Iron Chelating Agents; deferipron; Dopamine; Deferasirox; deferasirox; PC12 Cells; krysa rodu Rattus; chelátory železa; oxidační stres; katecholaminy; Rats; železo; Iron Overload; deferoxamin; Oxidopamine; Deferiprone; zvířata; oxidopamin